After critical care: Patient support after critical care. A mixed method longitudinal study using email interviews and questionnaires. Issue 4 (August 2015) - Pattison, Natalie; O'Gara, Geraldine; Rattray, Janice
Summary Purpose To explore experiences and needs over time, of patients discharged from ICU using the Intensive Care Experience (ICE-q) questionnaire, Hospital Anxiety and Depression Scale (HADS) and EuroQoL (EQ-5D), associated clinical predictors (APACHE II, TISS, Length of stay, RIKER scores) and in-depth email interviewing. Methods A mixed-method, longitudinal study of patients with >48 hour ICU stays at 2 weeks, 6 months, 12 months using the ICE-q, HADS, EQ-5D triangulated with clinical predictors, including age, gender, length of stay (ICU and hospital), APACHE II and TISS. In-depth qualitative email interviews were completed at 1 month and 6 months. Grounded Theory analysis was applied to interview data and data were triangulated with questionnaire and clinical data. Results Data was collected from January 2010 to March 2012 from 77 participants. Both mean EQ-5D visual analogue scale, utility scores and HADS scores improved from 2 weeks to 6 months, (p = <0.001; p = <0.001), but between 6 and 12 months, no change was found in data from either questionnaire, suggesting improvements level off. These variations were reflected in qualitative data themes: rehabilitation/recovery in the context of chronic illness; impact of critical care; emotional and psychological needs (including sub-themes of: information needs and relocation anxiety). The overarching, core theme related to adjustment of normality. Conclusions Patient recovery in this population appears to be shaped by ongoing illness and treatment. Email interviews offer a convenient method of gaining in-depth interview data and could be used as part of ICU follow-up.